Atrial Natriuretic Peptide Acts as a Neuroprotective Agent in in Vitro Models of Parkinson’s Disease via Up-regulation of the Wnt/β-Catenin Pathway - Colini Baldeschi, Arianna; Pittaluga, Eugenia; Andreola, Federica; Rossi, Simona; Cozzolino, Mauro; Nicotera, Giuseppe; Sferrazza, Gianluca; Pierimarchi, Pasquale; Serafino, Annalucia (Frontiers in Aging Neuroscience, 2018)
In the last decades increasing evidence indicated a crucial role of the Wnt/β-catenin signaling in development of midbrain dopaminergic (mDA) neurons. Recently dysregulation of this pathway has been proposed as a novel pathomechanism leading to Parkinson’s Disease (PD) and some of the molecules participating to the signaling have been evaluated as potential therapeutic targets for PD. Atrial natriuretic peptide (ANP) is a cardiac-derived hormone having a critical role in cardiovascular homeostasis. ANP and its receptors (NPRs) are widely expressed in mammalian central nervous system (CNS) where they could be implicated in the regulation of neural development, synaptic transmission and information processing, as well as in neuroprotection. Until now, the effects of ANP in the CNS have been mainly ascribed to the binding and activation of NPRs. We have previously demonstrated that ANP affects the Wnt/ß-catenin signaling in colorectal cancer cells through a Frizzled receptor-mediated mechanism. The purpose of this study was to investigate if ANP is able to exert neuroprotective effect on two in vitro models of PD, and if this effect could be related to activation of the Wnt/ß-catenin signaling. As cellular models of DA neurons, we used the proliferating or RA-differentiated human neuroblastoma cell line SH-SY5Y. In both DA neuron-like cultures, ANP is able to positively affect the Wnt/ß-catenin signaling, by inducing β-catenin stabilization and nuclear translocation. Importantly, activation of the Wnt pathway by ANP exerts neuroprotective effect when these two cellular systems were subjected to neurotoxic insult (6-OHDA) for mimicking the neurodegeneration of PD. Our data support the relevance of exogenous ANP as an innovative therapeutic molecule for midbrain, and more in general for brain diseases for which aberrant Wnt signaling seems to be involved.